Efektivitas Diklat Karya Tulis Ilmiah terhadap Kompetensi Menulis Widyaiswara - Nanan Nahriah (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2020)
[THE EFFECTIVENESS OF THE TRAINING OF SCIENTIFIC PAPERS ON WIDYAISWARA WRITING COMPETENCE] The purpose of this study is to describe the effectiveness of the training of scientific article on widyaiswara writing competence regarding the formulation of research problems, the formulation of theoretical studies, the formulation of research methods, the preparation of results and discussion, and the presentation of conclusions and suggestions. This research is a qualitative descriptive study. The research was carried out in the Education and Religious Technical Training Center. The research subjects were 10 widyaiswara who had participated in the training on scientific writing. Data collection techniques are documentation studies while data analysis techniques are using qualitative data analysis techniques. The results of the study showed that the training of scientific writing for widyaiswara was effective in developing the widyaiswara's competence in writing scientific papers. It revealed that all documents had included research problems in the introduction, content, and closing, although the terminology is not exactly the same as the writing guidelines but the essence is relevant to the problem. Some are explicitly disclosed and some are implicitly. Based on the results of the study, the researcher proposed a suggestion that the Pusdiklat continue to program scientific papers training for Widyaiswara.